The perils of self‐brand connections: Consumer response to changes in brand meaning. Issue 11 (1st August 2018) - Gaustad, Tarje; Samuelsen, Bendik M.; Warlop, Luk; Fitzsimons, Gavan J.
Abstract: Companies commit considerable resources to building brand associations that resonate with consumers' identities and facilitate strong consumer–brand bonds. The current research investigates a potential disadvantage of this popular strategy. The results from three studies show that consumers with a high degree of self‐brand connection respond negatively to brand developments (e.g., brand acquisitions and repositioning) that change brand meaning. The authors show that this effect is due to a change in the identity signaled by the brand. The results contrast with existing research, which has consistently found that brand connections promote probrand behavior and serve as a buffer against negative brand information.